ANALISIS FAKTOR - FAKTOR INOVASI KEUANGAN TERHADAP PENGUATAN FUNGSI INTERMEDIASI BRANCHLESS BANKING DI INDONESIA (STUDI KASUS BANK BUKU-4) - Lestari, Tantiana Anggi; Yenny Kornitasari (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2024)
Financial innovation was created to make it easier for banks to carry out their intermediation functions. There are many forms of financial innovation that exist today, but in this research the author focuses more on his analysis of strengthening the banking intermediation function through the Branchless Banking system with a sample of BUKU 4 banks (Business Group 4 Commercial Banks). In this research the author used primary data obtained through the results of distributing questionnaires online. From this research it can be concluded that the existence of Branchless Banking really helps banking institutions in carrying out their function as public financial distribution institutions and the existence of this system still does not shift the main role of banking institutions in carrying out their function as financial mediators in society.